Bahasa Inggris - Imawati, Iftitah; Galang Ismu Kurniawan; Muhammad Rifan Ghifari; Muhammad Nauval; Fajar Arisandi; Hendra Setiawan; Husein Mubarok (JURNAL NASIONAL TEKNIK ELEKTRO, 2025)
The growing demand for electricity and the environmental impact of fossil fuels have driven the need for alternative, sustainable energy solutions. Hydropower, particularly in irrigation channels, offers a promising option for generating renewable energy. This study focused on developing a small-scale pico-hydro system to generate electricity from water flow in irrigation channels, designed for applications such as street lighting. The research contributes to advancing micro-hydropower technology by integrating an Internet of Things(IoT)-based monitoring system to optimize energy production and simplify performance tracking. The monitoring system enabled real-time tracking of generator output, battery voltage, and load current using a smartphone interface connected via the internet. The study involved laboratory and field testing in some irrigation canals in Yogyakarta, Indonesia. A water wheel turbine from galvanized plates and plastic converts water flow into electrical energy. Field tests confirmed the system’s ability to produce stable power. The system reached an overall efficiency of 11.38%. The data transmission delay through Blynk averaged 5.64 seconds, while total power consumption was 2,231 watts. Sensor measurements showed high accuracy, with generator voltage accuracy at 99.33% and load current accuracy at 99.26%. In conclusion, the pico-hydro system can effectively harness irrigation water for small-scale power generation, offering a viable, renewable energy source with efficient remote monitoring capabilities